2014
DOI: 10.1016/j.tibs.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Serine and glycine metabolism in cancer

Abstract: HighlightsSerine and glycine are essential metabolites for cancer cells.Serine and glycine provide precursors for macromolecules and antioxidant defence.Metabolic enzymes of serine and glycine biosynthesis are upregulated in cancer.Innovative anticancer therapy is aiming to target serine and glycine biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
740
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 845 publications
(759 citation statements)
references
References 58 publications
(48 reference statements)
18
740
1
Order By: Relevance
“…Furthermore, downregulation of cMyc by shRNAs attenuated nutrient deprivation-induced high expression of SSP enzymes in Hep3B cells ( Figure 2E), suggesting that cMyc is critical for nutrient starvation-induced SSP activation. Finally, NMR analysis using 13 C-labeled glucose demonstrated that 13 C incorporation into both glycine and GSH was significantly increased in cMyc-overexpressing Hep3B cells ( Figure 2F), further demonstrating that cMyc promotes SSP activation, driving metabolic flux to glycine and GSH. Our data also showed that cMyc regulates glutaminolysis and glycolysis enzymes both at mRNA and protein levels in Hep3B cells (Supplementary information, Figure S1D-S1F).…”
Section: The Pathways Leading To Serine Biosynthesis Are Activated Unmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, downregulation of cMyc by shRNAs attenuated nutrient deprivation-induced high expression of SSP enzymes in Hep3B cells ( Figure 2E), suggesting that cMyc is critical for nutrient starvation-induced SSP activation. Finally, NMR analysis using 13 C-labeled glucose demonstrated that 13 C incorporation into both glycine and GSH was significantly increased in cMyc-overexpressing Hep3B cells ( Figure 2F), further demonstrating that cMyc promotes SSP activation, driving metabolic flux to glycine and GSH. Our data also showed that cMyc regulates glutaminolysis and glycolysis enzymes both at mRNA and protein levels in Hep3B cells (Supplementary information, Figure S1D-S1F).…”
Section: The Pathways Leading To Serine Biosynthesis Are Activated Unmentioning
confidence: 83%
“…As shown in Figure 3L, 13 C incorporation into both AMP and UMP was significantly increased in cMycor PSPH-overexpressing cells, and knocking down cMyc or PSPH markedly reduced 13 C incorporation into both AMP and UMP, suggesting that both cMyc and PSPH facilitate nucleotide synthesis, which could possibly account for the decreased S phase populations in PSPH-deficient cells ( Figure 3J). Importantly, knockdown of PSPH markedly inhibited cell proliferation in Hep3B and SK-hep-1 cells ( Figure 3M and Supplementary information, Figure S2E).…”
Section: Cmyc-mediated Psph Expression and Ssp Activation Are Criticamentioning
confidence: 86%
See 1 more Smart Citation
“…The GSH-dependent antioxidant response of cancer cells may benefit depending on the availability of serine, which can be transformed into glycine through the serine hydroxymethyltransferase (SHMT). [104][105][106] Interestingly, it has been demonstrated that cancer cells lacking p53 are protected from oxidative stress-induced by serine depletion in the presence of p73, a p53 family member that has the ability to drive serine biosynthesis de novo 107,108 and to increase the pentose phosphate shunt and nucleotide biosynthesis via G6PD. 109,110 Thus, the p73 overexpression detected in various primary RMS samples 111 may have an important role for oxidative stress resistance.…”
Section: Oxidative Stress Pathwaysmentioning
confidence: 99%
“…As such, PEPCK's role can be exploited for cancer therapy. Most recently, the role of serine and glycine has been appreciated in cancer [116]. Cancer cells uptake glucose and glutamine to produce serine and glycine, using intermediate metabolites of glycolysis and glutaminolysis.…”
Section: Oncometabolites For Synthesis Of Biomass and Malignancymentioning
confidence: 99%